Bharatidasan: Selected poems - Bharathidasan; BHARATHIDASAN; GANAPATHY (R) Tr; THANGAPPA (M Lenin) Tr (Pondicherry; Pondicherry Institute of Linguistics and Culture, 1996)
Bharathidasans Tamil poems translated in English
Keywords: Indian English Poetry; Indian English Literature